O desenho universal para a aprendizagem em tempos de escolas neoliberais: contribuições para uma educação inclusiva - Gueudeville, Rosane Santos (2024)
The dissemination of the Special Education model from an inclusive perspective began in the 1990, specifically through the inclusion of Target Audience students for Special Education in regular schools as a legal prerogative expressed by the Law of Guidelines and Bases of National Education and later by the National Policy for Special Education from the perspective of Inclusive Education, although we have observed a continuous increase in the proportion of enrollments - greater access - of students who are the target audience of special education, to regular schools, expressed through statistical summaries of Basic Education and microdata from the School Census, and such confirmation may demonstrate the guarantee of legal compliance, such data are still not very expressive to reveal the conditions of permanence, participation, and learning of these students. Therefore, more than pointing out merely quantitative indexes, it is important to understand under which rules and logic the principles of the right to education have been legitimized, because it may seem that such students, in this case, would “cease” to be excluded and would start to be included as students with disabilities, especially in times of neoliberal schools. To this end, we chose the objective of this research to enable the use of the principles of Universal Design for Learning (UDL) in “closed” educational contexts, aiming to promote inclusive pedagogical practices. This qualitative study was based on collaborative research in a regular school in Crato-CE. The participants were 05 teachers from the regular classroom and 02 teachers from the Multifunctional Resource Room. Data collection took place from April to December 2023, subject to approval by the Ethics Committee. We used a semi-structured interview script; the interviews were recorded using a cell phone or a Sony ICD-PX470 Digital Voice Recorder, transcribed entirely, and subjected to content analysis. After exhaustive reading of the interviews, we sought to define the “emic” categories that emerged from the subjects’ speeches. Subsequently, we conducted classroom observations and reformulated the planning based on the principles of Universal Design for Learning (UDL). The findings of this investigation indicated that pedagogical practices have been, for the most part, based on the transmission of content; teaching work tends to be solitary (there is generally no interdisciplinary dialogue); the teaching process tends to have a technical conception; students with special educational needs are exclusively under the responsibility of their caregivers; the routine is almost always centered on the book and that the indexes of external evaluations “determine” and “guide” the pedagogical practices. After the intervention with the UDL, we noticed significant changes in the teaching and learning process, so that the students were more engaged, the contents were made possible through multiple modes of representation and the students had different opportunities for action and expression. Therefore, we believe that the UDL can, in fact, contribute in different ways to eliminate/minimize the barriers to learning for all students, even in neoliberal educational contexts.